Why Do Banking Crises Occur? the American Subprime Crisis Compared with the Norwegian Banking Crisis 1987-92 - Sverre Knutsen (Norges Bank, 2012)
This paper analyses the causes of banking crises by the way of a historical comparative case study. Moreover, the analysis draws on theories elaborated by the economist Hyman Minsky. The evidence presented suggests that the fundamental causes of the compared crises are found in the macroeconomic boom-bust fluctuation and the building up of asset market bubble(s) preceding the breakdown and the crisis. We also find boom-bust cycles as depicted in a basic Minsky-cycle, where financial instability and the outbreak of crisis is a consequence of an unbalanced mix of hedge, speculative and Ponzi financial positions. In both cases we have observed a pattern where stabilizing or thwarting institutions, as Minsky denoted them, were eroded over time. Each case demonstrates that structural economic shifts were interacting with major institutional changes and created processes that effectively removed institutional stabilizers. Hence, systemic risk was allowed to fill up the financial system. These processes were essential for building up financial imbalances of such a magnitude that the particular booms ended in systemic banking crises.
hdl:11250/2496811
Keywords: E32; E51; G01; G18; N10; N12; N14; 330; financial crisis; business cycles; institutional stabilizers; structural economic change; liberalization